Sistem Informasi Penjualan Dan Persediaan Barang Pada PT. Bali Murni - wildahlia, ayu gede; Deastika, Putu Ayu (INFOTEKS (Information Technology, Computer and Sciences), 2022)
Sales and inventory information system at PT. Bali Murni is a system that has the ability to manage user data, customer data, supplier data, order confirmation data, goods data, purchase order data, sales transaction data and report generation. This system is managed by marketing, accounting and director. In this case, PT. Bali Murni is used as a research place, because the sales and inventory information system in that place has not been managed properly so that errors often occur in the preparation of existing reports. This study aims to design and build a sales and inventory information system that can provide convenience during the processing of customer, supplier and goods data, minimize errors in the order confirmation process, PO, and sales transactions, minimize errors in reporting on PT. Pure Bali. In the results of the study, a sales and inventory information system has been developed at PT. Pure Bali. In building this system using the programming language PHP, HTML and MySQL as the database. This system is tested where the scenarios that have been created are carried out in black boxes with the expected results and obtain valid overall test results or as expected.